2016
DOI: 10.1007/s00264-016-3358-1
|View full text |Cite
|
Sign up to set email alerts
|

Off-loading strategies in diabetic foot syndrome–evaluation of different devices

Abstract: A customized device like the TCC is still the most proven offloading device. However, a removable cast walker being based on vacuum pads and a cushioning sole, provides better results concerning force distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 21 publications
2
56
0
2
Order By: Relevance
“…One RCT found a significantly greater plantar pressure reduction from barefoot pressure baselines in a knee‐high walker compared with a TCC at the ulcer site (91% vs 80%), the forefoot (92% vs 84%), and midfoot (77% vs 63%) (all, P < 0.05), but no difference in the heel ( P = 0.11) . However, several noncontrolled cross‐sectional studies found no significant difference in plantar pressure reduction from standard footwear baselines in knee‐high walkers compared with TCCs at the ulcer site, hallux, and forefoot . We found no controlled studies investigating weight‐bearing activity.…”
Section: Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…One RCT found a significantly greater plantar pressure reduction from barefoot pressure baselines in a knee‐high walker compared with a TCC at the ulcer site (91% vs 80%), the forefoot (92% vs 84%), and midfoot (77% vs 63%) (all, P < 0.05), but no difference in the heel ( P = 0.11) . However, several noncontrolled cross‐sectional studies found no significant difference in plantar pressure reduction from standard footwear baselines in knee‐high walkers compared with TCCs at the ulcer site, hallux, and forefoot . We found no controlled studies investigating weight‐bearing activity.…”
Section: Recommendationsmentioning
confidence: 99%
“…One high‐quality RCT found a removable knee‐high device (bivalved TCC) showed greater plantar pressure reductions from standard footwear baseline levels at the ulcer site than a removable ankle‐high cast shoe or forefoot offloading shoe (67% vs 47% vs 26%, respectively, P = 0.029) . Several cross‐sectional studies also found that removable knee‐high devices show greater forefoot plantar pressure reduction than removable ankle‐high devices . Three RCTs investigated weight‐bearing activity.…”
Section: Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations